1998
DOI: 10.1016/s0735-1097(98)00351-9
|View full text |Cite
|
Sign up to set email alerts
|

Early age at repair prevents restrictive right ventricular (RV) physiology after surgery for tetralogy of Fallot (TOF)

Abstract: Restrictive RV physiology is inversely related to age at repair and independent of type of outflow tract repair. Since TAP repair is more common in early repair, and restriction seems to be less frequent, long-term follow-up to assess adverse effects of pulmonary regurgitation is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 18 publications
2
44
2
2
Order By: Relevance
“…Several studies have correlated preoperative and operative factors with restrictive right ventricular physiology; however, as in our study, few relevant data were found [1][2][3][4][5][6][7][8][9] . Restrictive right ventricular physiology may relate to a process of endomyocardial fibrosis intrinsic to the disease itself and intensified as time goes by 10 , to the ventriculotomy, and to the interposition of patches in the interventricular septum and in the infundibulum 3,4,6 .…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…Several studies have correlated preoperative and operative factors with restrictive right ventricular physiology; however, as in our study, few relevant data were found [1][2][3][4][5][6][7][8][9] . Restrictive right ventricular physiology may relate to a process of endomyocardial fibrosis intrinsic to the disease itself and intensified as time goes by 10 , to the ventriculotomy, and to the interposition of patches in the interventricular septum and in the infundibulum 3,4,6 .…”
Section: Discussioncontrasting
confidence: 71%
“…Its prevalence in the literature ranges from 28 to 52% 3,6 . In our study, with an intermediate postoperative follow-up, 63.3% of the patients had this alteration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations